Guided three-dimensional growth of functional cardiomyocytes on polyethylene glycol nanostructures - Kim, Deok-Ho (Langmuir : the ACS journal of surfaces and colloids, 2006)
We introduce well-defined nanopillar arrays of a poly(ethylene glycol) (PEG) hydrogel as a cell culture platform to guide a 3D construct of primary rat cardiomyocytes in vitro for potential tissue engineering applications. Ultraviolet (UV)-assisted capillary lithography was used to fabricate highly uniform approximately 150 nm PEG pillars with approximately 400 nm height. It was found that cell adhesion was significantly enhanced on PEG nanopillars (132 +/- 29 cells/mm2) compared to that on the bare PEG control (39 +/- 17 cells/mm2) (p < 0.05) but substantially reduced compared to that on the glass control (502 +/- 45 cells/mm2) (p < 0.01). Furthermore, in colonizing cardiomyocytes, the nanopillars stimulated self-assembled aggregates among the contacting cells with 3D growth, which is a unique feature for nanopatterned PEG hydrogels as a cell culture substrate. The 3D-grown cardiomyocytes retained their conductive and contractile properties, as evidenced by the observation of beating cardiomyocytes with robust action potential generation